2014
DOI: 10.4300/jgme-d-14-00128.1
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalized Patients' Perceptions of Resident Fatigue, Duty Hours, and Continuity of Care

Abstract: In a survey about physician attributes relevant to medical errors and patient safety, adult inpatients in a large and diverse sample reported greater concern about fatigue and working hours than about continuity of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
3
1
Order By: Relevance
“…Our patient results demonstrate that patients cared for by extended duty-hour interns do not note significant differences in their overall satisfaction, the amount they saw their medical team, how well the doctors knew their medical problems, or how well the doctors listened to them. Although prior literature has suggested that patients have greater concerns about fatigue and working hours than about continuity of care, 11 our data show no indication that the patients perceived differences between the 2 groups. However, in our study, patients were not informed of the differences in intern duty hours between the 2 units.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our patient results demonstrate that patients cared for by extended duty-hour interns do not note significant differences in their overall satisfaction, the amount they saw their medical team, how well the doctors knew their medical problems, or how well the doctors listened to them. Although prior literature has suggested that patients have greater concerns about fatigue and working hours than about continuity of care, 11 our data show no indication that the patients perceived differences between the 2 groups. However, in our study, patients were not informed of the differences in intern duty hours between the 2 units.…”
Section: Discussioncontrasting
confidence: 99%
“…However, these studies also noted that attitudes differed significantly between interns and program directors about the impact of shift length. [8][9][10] Although survey data have suggested that patients express greater concern about fatigue and working hours than about continuity of care, 11 little research has evaluated the effect of intern work hours on the patient experience as well as the perceptions of the other members of the interdisciplinary care team, such as nurses.…”
mentioning
confidence: 99%
“…[8][9][10][11] Long duty-hours have been linked to several resident, patient, and community safety concerns [12][13][14][15] . Likewise, patients do not appear to feel comfortable with physicians who worked long hours 5,6 . With these concerns, we argue that iCOMPARE should have demonstrated superiority of unrestricted shift lengths.…”
mentioning
confidence: 99%
“…Patients are both interested in, and concerned by, the length of their doctors' shifts 5 . Indeed, in one study, a significant number of patients stated they would like to be informed of any clinician who had worked over 12 hours 6 . Patients and residents deserve to be informed of factors affecting their care, particularly in a trial with the primary endpoint involving their 30-day mortality.…”
mentioning
confidence: 99%